Catalytic Synthesis of Hard/Soft Carbon Hybrids with Heteroatom Doping for Enhanced Sodium Storage. Issue 12 (28th March 2019) - Liu, Xu; Zhu, Youyu; Liu, Na; Chen, Mingming; Wang, Chengyang; Wang, Xiaolei
Abstract: Hard carbon shows a promising application for sodium storage but suffers from low electrochemical stability, which leads to poor rate capacity and cycle life. Here, we report a heteroatom‐doping hard/soft carbon hybrid prepared by easy oxidizing acid treatment and low temperature catalytic graphitization. The heteroatoms increase the sodium‐ion adsorption capability during slope region, showing an important contribution at high current. Besides, the introduction of oriented domains enhances the conductivity, as well as the heteroatom doping, and electrochemical stability of hard/soft carbon hybrids. What's more, these structure characteristics also benefit the stable storage of sodium ions, supported by a 74% increase in terms of reversible capacity. Thus, the electrochemical performance retains a fast and reversible capacity of 125 mAh⋅g −1 at high current density of 8 C. Abstract : The hard/soft carbon hybrids with heteroatom‐doping were prepared by oxidizing acid treatment and catalytic graphitization. Introducing more heteroatom enhances the capacity by absorption of Na + which shows vital performance of anode at high current. The introduction of oriented domains improves the electrochemical stability of electrode materials. With the two aspects of modification, the hard/soft carbon hybrid remains enhanced sodium storage.